Perbedaan Hasil Pemeriksaan Tes Cepat Molekuler Metode Genexpert dengan Sampel Ludah dan Dahak pada Pasien Terduga Tuberkulosis di Puskesmas Wanareja I Cilacap - Retno, Retno; Puspodewi, Dini; Pangesti, Ira (Innovative: Journal Of Social Science Research, 2025)
Tuberculosis (TB) is an infectious disease caused by the bacteria Mycobacterium tuberculosis (M. tuberculosis). The methods currently used in the diagnosis of TB cannot meet the requirements due to their low sensitivity. Molecular Rapid Tests (TCM) can produce different results because they require the doctor's accuracy in examining the results. One of the fastest methods available for diagnosis is the GeneXpert MTB/RIF test. GeneXpert is able to detect Mycobacterium tuberculosis that is resistant to Rifampicin. The use of the GeneXpert method can use saliva or sputum samples. The purpose of this study was to determine the difference in the results of the molecular rapid test using the Genexpert method with saliva and sputum samples in suspected tuberculosis patients. The research method used comparative research. A sample of 44 saliva and sputum samples in suspected tuberculosis patients at the Wanareja I Health Center. Data analysis using the chi square test. The results showed that there was a difference in the results of the molecular rapid test using the Genexpert method with saliva and sputum samples in suspected tuberculosis patients (pv = 0.000).